Potential Management And Utilization Levels Of Decaptureus macarells In Manado Bay - Lohoo, Anneke V. (Sam Ratulangi University, 2023)
This study aims to determine the meristic and morphometric characteristics of the flying catfish in Manado Bay. It is hoped that it will be useful in the optimal management process based on characteristics, and become reference material for policymakers, practitioners, and the public so that they are more concerned about the preservation of flying catfish, and serve as a basis for managing flying fish resources. Data for flying fish are taken from the Fish Auction Place (TPI), fishing boat landing sites, and several markets in Manado City. Measurement of morphometric and meristic data was carried out directly at the sampling location, including observations of fish fins and scales. Morphometric data analysis is presented in the total length frequency distribution graph. The relationship between two certain morphometric characters is determined by the formula: regression Y = a + b X and the correlation value is r to see the closeness of the relationship between the two characters. The relationship between the two calculated characters is presented in graphical form. The morphometric value of the blue swallow is obtained, namely the Y axis which is the same as FL with a value of 5.297, and the X axis which is the same as TL with a value of 0.887. Keywords: morphometrics, meristic, flying fish, Manado Bay Abstrak Penelitian ini bertujuan mengetahui karakter meristik dan morfometrik ikan layang di Teluk Manado. Diharapkan bermanfaat dalam proses pengelolaan secara optimal berdasarkan karakteristik, dan menjadi bahan referensi bagi pengambil kebijakan, praktisi, dan masyarakat agar lebih peduli dalam pelestarian ikan layang, serta dijadikan sebagai dasar dalam pengelolaan sumber daya ikan layang. Data ikan layang diambil dari Tempat Pelelangan Ikan (TPI), tempat pendaratan perahu nelayan, dan beberapa pasar di Kota Manado. Pengukuran data morfometrik dan meristik dilakukan secara langsung di lokasi pengambilan sampel, termasuk pengamatan sirip dan sisik ikan. Analisis data morfometrik disajikan dalam grafik sebaran frekuensi panjang total. Hubungan antara dua karakter morfomterik tertentu ditentukan dengan rumus : regresi Y = a + b X dan nilai korelasinya yakni r untuk melihat keeratan hubungan kedua karakter. Hubungan kedua karakter yang dihitung akan disajikan dalam bentuk grafik. morfometrik ikan layang biru diperoleh nilai yaitu sumbu Y yang sama dengan FL dengan nilai 5.297, dan sumbu X yang sama dengan TL dengan nilai 0.887. Kata kunci: morfometrik, meristik, ikan layang, Teluk Manado